Explaining the relationship between moral intelligence and professional self-concept with the competency of nursing students in providing spiritual care to promote nursing education - Narges Eskandari; Farzaneh Golaghaie; Maryam Aghabarary; Mohammadreza Dinmohammadi; Hamidreza Koohestani; Mojtaba Didehdar; Leila Dehghankar; Mohammad Abbasi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND AND AIM: Several factors are involved in obtaining the competence of providing spiritual care in nursing students. The purpose of this study was to explain the relationship between moral intelligence and the professional self-concept with the competency of the nursing students in providing spiritual care to promote nursing education. MATERIALS AND METHODS: The present study was descriptive-analytics and the participants were the 7th and 8th semester nursing students of the processing district 6 of the medical sciences universities. The data were collected using questionnaires "Nursing student competencies for providing spiritual care," "Nursing professional self-concept" and "Moral intelligence" questionnaire and analysed using correlation and regression tests. RESULTS: The results showed that there is a significant relationship between the moral intelligence and the students competency in providing spiritual care (r = 0.24, P < 0.001), while this relationship was not significant for the professional self-concept (r = 0.045). Furthermore, based on the results of multiple regression analysis, the moral intelligence (B = 0.28, P = 0.001), gender (B = −4.23, P = 0.048), place of living (B = 10.59, P = 0.046), and adherence to religion (B = −11.82, P = 0.002) were the predictors of students' competency in providing the spiritual care. CONCLUSION: According to the results of this study, it is suggested that by applying strategies to strengthen the moral intelligence of the students, such as holding-related workshops as well as reinforcing religiosity, the student's competency in providing the spiritual care to the patients is reinforced.